The role of demographics in citizens’ behavioral intentions for participatory forest management planning - Mohammadi, Zohreh; Kašpar, Jan; Tahri, Meryem (Frontiers in Forests and Global Change, 2025)
This study evaluated the influence of demographic variables on Czech citizens’ behavioral intentions (IN) to participate in forest management planning, by examining differences in the Theory of Planned Behavior (TPB) model across demographic groups. Structural Equation Modeling (SEM) with multi-group analysis was applied to test how age, gender, education, income, occupation, area of residence, and forest ownership moderated the relationships among attitude (AT), subjective norms (SN), and perceived behavioral control (PBC). The results revealed that gender, education, area of residence, and income significantly moderated the influence of TPB constructs on participatory intention, while age, occupation, and forest ownership inquiry showed weaker or non-significant effects. Females exhibited stronger SN effects (β = 0.929), whereas males relied more heavily on PBC (β = 1.065). Higher-income respondents (>1,600 EUR /month) demonstrated a stronger PBC effect (β = 0.597), while lower-income participants were more influenced by SN (β = 0.933). Participants with a high school education or less were slightly more influenced by SN (β = 0.902) compared to college-educated respondents (β = 0.703). Additionally, suburban and rural residents were slightly more influenced by PBC (β = 0.671), whereas urban residents were more influenced by SN (β = 0.629). These findings highlight the importance of demographic and experiential diversity in shaping environmental behavior and provide actionable insights for developing inclusive and effective participatory forest management strategies.